ZAKAT DAN INFAQ DALAM MENGURANGI PATOLOGI KEMISKINAN ( STUDI PADA BAITUL MAL KOTA LANGSA) - Kamal, Safwan (Fakultas Ekonomi dan Bisnis Islam, 2018)
The purpose of this study is to find out how the concepts of zakat and infaq management exist in the Baitul Mal City of Langsa and how economic values ​​are motivated in the concept in reducing the pathology of poverty. With the phenomenology approach this study found that the management of zakat is carried out in reducing the pathology of poverty carried out in productive form with a full ownership mechanism, while infaq is carried out in the form of unsecured revolving financing programs. Build emotional closeness with mustahiq to keep trying. Second: Building responsibility for improving economic status. Third: Building work motivation. Fourth: Building independence. Fifth: Build self-confidence to achieve success in business. Sixth: Building social responsibility in the community. The economic motivation values ​​realized through productive infaq programs are: First: Building business references as a reference for increasing income. Second: Building relationships with members recommending mustahik to take part in training and business coaching. Third: Build market references in developing businesses. Fourth: Build ideology to read new business opportunities in increasing income.